Testing the Inclination of an Industrial Diesel Engine Under Static Conditions According to the International Convention for the Safety of Life at Sea (SOLAS) Regulations - Suardi; Muhdar Tasrief; Samsu Dlukha Nurcholik; Amalia Ika Wulandari; Wira Setiawan (International Journal of Marine Engineering Innovation and Research, 2023)
Many industrial diesel engines are used as the main engine of the ship. Apart from being relatively cheaper, the availability of industrial engine is also very abundant, and the repair process is also not too complicated. However, when viewed from the SOLAS regulations related to the main requirements for a ship propulsion engine, it must also be considered, because it operates at sea, so that ship engines must be tougher than industrial engines, especially related to engine performance when experiencing rolling and trim. The purpose of this research is to test the feasibility of industrial diesel engines being operated on ships. By using a water-cooled single-cylinder diesel engine which is commonly used in small ships. The experimental method was used in this research to obtain optimal results according to the conditions in the field, the engine was made in three variations, namely the normal condition (without inclination angle), the rolling condition of 150, and the trim condition of 50 which complies with SOLAS regulations related to the inclination angle. The results of the research obtained torque, Specific Fuel Consumption (SFC), and engine thermal efficiency in various engine variations. The highest torque is in the condition of the 150 rolling engine, which is 13.87 N.m. The lowest SFC is in the condition of the 150 rolling engine, which is 194 gr/kW.h. and the highest thermal efficiency was also obtained at the condition of the 150 rolling engine, namely 44.9%. The higher the engine speed, the higher the engine performance value in rolling 150 conditions, and the 50 trim conditions experience an increasing trend, but in low rotation conditions (750 Rpm) the performance decreases. Seeing the results obtained, a water-cooled single-cylinder diesel engine can be used as a small boat propulsion engine.